Estudio técnico táctico del voleibol, en las deportistas de la categoría media y la construcción de un modelo biomecánico de la técnica del remate. Año 2014 - Macas Torres, Jairo Israel (2014)
This research I structure based on the central problem, how it affects tactical technical study of volleyball athletes in the middle category and the construction of a biomechanical model of the art auction. 2014, just as in relation to the central problem and the problems arising from raised the overall objectives analyze the kick volleyball, through a tactical and technical biomechanical study to improve performance and prevent injury. The specific objectives. Identify technical and tactical qualities volleyball athletes in the Mid intercollegiate championship Compiling the information obtained to build a biomechanical model. Contribute with a biomechanical model of the art auction to improve performance and injury prevention. For the scope -. Research will be conducted under a qualitative approach on the place. - This is a descriptive study, which is generated from the auction to improve the women's volleyball team and its impact on the Intercollegiate Championship. It allowed me to apply various methods to reach conclusions and recommendations such as the Scientific Method. To get to know the problems that investigated the empirical method it allowed me to know the reality, also the Inductive-Deductive Method was used was used -. Using this information was available you will see the individual cases that present such problems and it was the technique of determining who gets in their implementation and subsequently became general conclusions about how this problem is in the school's Immaculate. The Hypothetical Method was used to conduct a thorough observation of the problem to investigate proceeded to approach the hypothesis The research population is 12 volleyball players in the middle category of educational institution in the Immaculate techniques that use was the art of observation, the technique of the art test survey. The results were obtained from the application of different techniques and instruments the same as those placed in tables and graphs and then make a conceptual analysis and compare it with reality investigated with these results we used for the discussion of the hypotheses the same they are with their cause and effect variables reaching the same test hypotheses that allowed me to reach the conclusions recommendations kick technique directly affects the execution of the tactics of volleyball as a biomechanical model finally proposed methodology was applied to the to improve kick technique in volleyball.